Strategi Kepala Sekolah dalam Meningkatkan Prestasi Non Akademik Peserta Didik di SDN 081 Panyabungan - Risma Harahap; Ali Yusron; Reni Septrisia (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
"School Principal's Strategy for Improving Non-Academic Achievement of Students at SDN 081 Panyabungan". Student achievement is important because a school is most often and generally in the spotlight, namely the achievements obtained by students in both academic and non-academic fields. The achievement data for SDN 081 Panyabungan shows several non-academic achievements from 2017-2023, up to 24 non-academic achievements that have been achieved in those 6 years. This research aims to: 1) The principal's strategy in improving the non-academic achievement of students at SDN 081 Panyabungan, 2) Analysis of the interests and talents of students at SDN 081 Panyabungan, 3) Supporting and inhibiting factors for the principal's strategy in improving the non-academic achievement of participants Educated at SDN 081 Panyabungan. This research is a type of qualitative research with a descriptive approach with data analysis techniques, namely data collection, data reduction, drawing conclusions and presenting data. The research results found that 1) The principal's strategy in improving the non-academic achievement of students at SDN 081 Panyabungan uses management functions, namely planning, organizing, implementing, supervising. 2) Analysis of students' interests and talents, namely conducting surveys and interviews to find out interests and talents, asking what activities they like and activities they want to develop, 3) Supporting and inhibiting factors in implementing the principal's strategy in improving students' non-academic achievements, namely internal factors (interests and talents) and external factors (parents, society, school). The conclusion of this research is that non-academic education strategies are important for school principals and teachers to understand and pay attention to students' needs. Support from teachers, parents, the community and the school committee is also very important to achieve the goal of improving students' non-academic achievements.